The European Registry for Patients with Mechanical Circulatory Support of the European Association for Cardio-Thoracic Surgery: third report - de By, Theo M M H; Schoenrath, Felix; Veen, Kevin M; Mohacsi, Paul; Stein, Julia; Alkhamees, Khalid M M; Anastasiadis, Kyriakos; Berhnardt, Alexander; Beyersdorf, Friedhelm; Caliskan, Kadir; Reineke, David; Damman, Kevin; et al. (European journal of cardio-thoracic surgery, 2022)
OBJECTIVES: In the third report of the European Registry for Patients with Mechanical Circulatory Support of the European Association for Cardio-Thoracic Surgery, outcomes of patients receiving mechanical circulatory support are reviewed in relation to implant era. METHODS: Procedures in adult patients (January 2011-June 2020) were included. Patients from centres with <60% follow-ups completed were excluded. Outcomes were stratified into 3 eras (2011-2013, 2014-2017 and 2018-2020). Adverse event rates (AERs) were calculated and stratified into early phase (<3 months) and late phase (>3 months). Risk factors for death were explored using univariable Cox regression with a stepwise time-varying hazard ratio (<3 vs >3 months). RESULTS: In total, 4834 procedures in 4486 individual patients (72 hospitals) were included, with a median follow-up of 1.1 (interquartile range: 0.3-2.6) years. The annual number of implants (range: 346-600) did not significantly change (P = 0.41). Both Interagency Registry for Mechanically Assisted Circulatory Support class (classes 4-7: 23, 25 and 33%; P < 0.001) and in-hospital deaths (18.5, 17.2 and 11.2; P < 0.001) decreased significantly between eras. Overall, mortality, transplants and the probability of weaning were 55, 25 and 2% at 5 years after the implant, respectively. Major infections were mainly noted early after the implant occurred (AER<3 months: 1.44 vs AER>3 months: 0.45). Bilirubin and creatinine levels were significant risk factors in the early phase but not in the late phase after the implant. CONCLUSIONS: In its 10 years of existence, EUROMACS has become a point of reference enabling benchmarking and outcome monitoring. Patient characteristics and outcomes changed between implant eras. In addition, both occurrence of outcomes and risk factor weights are time dependent.
Keywords: výsledek terapie; Heart-Assist Devices; srdeční selhání; hrudní chirurgické výkony; Mechanical circulatory support; Adult; Thoracic Surgical Procedures; dospělí; registrace; hrudní chirurgie; Treatment Outcome; lidé; Heart Failure; Humans; Registry; podpůrné srdeční systémy; Thoracic Surgery; Registries; End-stage heart failure; Ventricular assist device